A Joint Vehicle-Vehicle/Vehicle-Roadside Communication Protocol for Highway Traffic Safety. (11th April 2011) - Hu, Bin; Gharavi, Hamid
Abstract : A joint vehicle-vehicle/vehicle-roadside communication protocol is proposed for cooperative collision avoiding in Vehicular Ad Hoc Networks (VANETs). In this protocol, emergency warning messages are simultaneously transmitted via Vehicle-to-Vehicle (V2V) and Vehicle-to-Roadside (V2R) communications in order to achieve multipath diversity routing. In addition, to further improve communication reliability and achieve low latency, a Multi-Channel (MC) technique based on two nonoverlapping channels for Vehicle-Vehicle (V2V) and V2R (or R2V) is proposed. The simulation results demonstrate that the proposed joint V2V/V2R (R2V) communication protocol is capable of improving the message delivery ratio and obtaining low latency, which are very important merits for highway traffic safety.